Norovirus molecular trends in Harbin preschoolers Post-NPI easing - Yuan Tian; Xiqiao Du; Hong Gao; Mingyue Yuan; Yingchen Wang; Lei Shang; Yuhui Pan; Tuo Dong; Zhe Zhang (Journal of Infection and Public Health)
Background: Noroviruses (NoV) are key pathogens causing acute gastroenteritis (AGE) in children, with a significant disease burden, especially in developing nations. This study aims to track changes in NoV genotype epidemiology before and after the lifting of COVID-19 non-pharmacological interventions (NPIs) in Harbin. Methods: In this study, we investigated fecal samples collected by the Harbin Children's Hospital from attended AGE preschoolers between January 2022 and December 2023. The detection of norovirus was performed using RT-qPCR. Later, the norovirus-positive samples were typed by conventional RT-PCR and Sanger sequencing. Phylogenetic analysis, recombination breakpoint analysis, and mutation analysis were also performed. Results: 230 NoV-positive samples were detected in the two years, with a positive rate of 39.1 %, belonging to NoV GⅡ. According to the partial sequences of the RNA-dependent RNA polymerase (RdRp) and VP1 gene sequence analysis, seven different genotypes were detected, being GII.4[P16] (61.5 %) the predominant one. Furthermore, the mutation analysis indicated that Harbin-Nov-066–2023 exhibited a mutation from valine to isoleucine at positions 290aa and 386aa in the VP1 region, respectively, compared to Harbin-Nov-022–2022. Additionally, strains from the rare type GⅡ.8[P8] were detected in 2022. Conclusions: These findings may contribute novel data to the genetic database of norovirus in Harbin. This could facilitate investigations into the genetic evolution of this virus, developing vaccines to target dominant genotypes and the molecular basis of norovirus genetics.